Dynamic changes of bone metastasis predict bone‐predominant status to benefit from radium‐223 dichloride for patients with castration‐resistant prostate cancer. (22nd September 2020) - Hashimoto, Kohei; Miyoshi, Yasuhide; Shindo, Tetsuya; Hori, Masakazu; Tsuboi, Yasumasa; Kobayashi, Ko; Fukuta, Fumimasa; Tanaka, Toshiaki; Miyamoto, Shintaro; Maehana, Takeshi; Okada, Manabu; Nishiyama, Naotaka; et al.
Abstract: Background: To best employ radium‐223 dichloride (Ra‐223) for patients with castration‐resistant prostate cancer (CRPC) and bone metastasis, we investigated the bone‐predominant status in patients treated with Ra‐223. Methods: We retrospectively evaluated 127 CRPC patients who underwent treatment with Ra‐223. The patients were divided into three groups based on the types of dynamic changes of bone metastasis between diagnosis and just before Ra‐223: (a) only known lesions; (b) de novo lesions; (c) new progressive lesions. We developed the risk assessment using predictive factors based on progression‐free survival (PFS). Results: During the median follow‐up period of 10.4 months, the median PFS in the only known lesions group was 11.3 months compared to 8.1 months in the de novo lesions group and 5.1 months in the new progressive lesions group ( P  < .001). In multivariate analysis, the type of the new progressive lesions in bone metastasis (HR 1.45, 95% CI 1.13‐1.66, P  = .003), performance status of >1 (HR 1.74, 95% CI 1.04‐2.89, P  = .034), PSA value of >100 ng/mL (HR 1.59, 95% CI 1.02‐2.50, P  = .043), and PSA doubling time (PSADT) of <3 months (HR 1.53, 95% CI 1.11‐2.03, P  = .007) were independent unfavorable predictive factors for PFS. The risk assessment for PFS was highlighted when the type of dynamic changes of bone metastasis was combined with PSADT just before Ra‐223 treatment. This was associated with non‐bone metastasis progression, especially visceral metastasis, and overall survival. Conclusions: Risk assessment in combination with dynamic changes of bone metastasis and PSADT determines the bone‐predominant metastasis type to benefit from Ra‐223. Abstract : We developed the risk assessment based on the types of dynamic changes of bone metastasis before the use of radium‐223 dichloride (Ra‐223). This risk assessment can be used to maximize the clinical benefits of Ra‐223 treatment for bone‐predominant metastasis.